Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1002/ejoc.200800900
|View full text |Cite
|
Sign up to set email alerts
|

1,2,4,5‐Tetrakis(tetramethylguanidino)benzene: Synthesis and Properties of a New Molecular Electron Donor

Abstract: The molecular electron donor 1,2,4,5-tetrakis(tetramethylguanidino)benzene (ttmgb) was synthesised by reaction between 1,2,4,5-tetraaminobenzene and 2-chloro-1,1Ј,3,3Ј-tetramethylformamidinium chloride. Protonation and oxidation of the molecule were analysed. In the course of titration of initially yellow-coloured solutions of ttmgb with HCl intense and fully reversible colour changes were observed; the diand tetraprotonated forms are green-and blue-coloured, respectively. The tetraprotonated molecule crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
132
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 97 publications
(141 citation statements)
references
References 37 publications
6
132
0
3
Order By: Relevance
“…of 1 in CH 3 CN. Although CH 3 CN was shown to be reactive in our previous work, [6] the experiments indicate that CH 3 CN deprotonation does not occur in the presence of acetylenes in the solution. Two types of products were isolated.…”
Section: Synthesis and Structural Characterisationmentioning
confidence: 79%
See 2 more Smart Citations
“…of 1 in CH 3 CN. Although CH 3 CN was shown to be reactive in our previous work, [6] the experiments indicate that CH 3 CN deprotonation does not occur in the presence of acetylenes in the solution. Two types of products were isolated.…”
Section: Synthesis and Structural Characterisationmentioning
confidence: 79%
“…More intriguing, the reaction does not work if 1 is replaced by the stronger base 2 [1,2,4,5-tetrakis(tetramethylguanidino)benzene, see Scheme 2, pK a = 25.3 for 2 in CH 3 CN]. [6] Scheme 2.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…[17] With the synthesis of guanidino-functionalized aromatics (GFAs), [18] our group developed a new class of redox-active ligands with strong electron-donating abilities. Initial studies focused on 1,2,4,5-tetrakis(tetramethylguanidino)benzene (3) [19] (see Scheme 1), 1,4,5,8-tetrakis(tetramethylguanidino)naphthalene (4), [20] and 2,3,5,6-tetrakis(tetramethylguanidino)pyridine (5) [21] (see Scheme 2).The Lewis structures explaining the redox activity of these GFA ligands are comparable with those for the oxidation of o-dioxolene ligands (e.g. twofold deprotonated catechol 1) and the tetraoxolene tetraanion 2.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, some of us recently showed that tetrakis(tetramethylguanidino)benzene (ttmgb; see Scheme 1) can be oxidized readily, for example, by O 2 in the air or by I 2 . [10] A two-electron oxidation wave was measured at E 1/2 A C H T U N G T R E N N U N G (CH 3 CN) = À0.32 V versus SCE (see Figure S1 in the Supporting Information). In its oxidized form, the positive charges are delocalized, with two of the resonance structures being sketched in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%